2022
DOI: 10.1007/s11211-022-00389-0
|View full text |Cite|
|
Sign up to set email alerts
|

Deliberating Inequality: A Blueprint for Studying the Social Formation of Beliefs about Economic Inequality

Abstract: In most contemporary societies, people underestimate the extent of economic inequality, resulting in lower support for taxation and redistribution than might be expressed by better informed citizens. We still know little, however, about how understandings of inequality arise, and therefore about where perceptions and misperceptions of it might come from. This methodological article takes one step toward filling this gap by developing a research design—a blueprint—to study how people’s understandings of wealth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, our assessment of meritocratic beliefs is necessarily restricted to a single measure which examines respondent's tendency to explain success through individual versus structural (or a mix of both) factors. In the context of rising economic inequality (Gornick and Jantti 2013;Piketty 2014), we argue that the research literature can benefit from a more comprehensive understanding of the determinants of such attitudes (Summers et al 2022).…”
Section: Inequality Attitudes and Beliefsmentioning
confidence: 95%
See 3 more Smart Citations
“…Meanwhile, our assessment of meritocratic beliefs is necessarily restricted to a single measure which examines respondent's tendency to explain success through individual versus structural (or a mix of both) factors. In the context of rising economic inequality (Gornick and Jantti 2013;Piketty 2014), we argue that the research literature can benefit from a more comprehensive understanding of the determinants of such attitudes (Summers et al 2022).…”
Section: Inequality Attitudes and Beliefsmentioning
confidence: 95%
“…On the other hand, nations with a "communist history" are more likely to be skeptical of large income differences (Hadler 2005;Kunovich and Słomczy nski 2007). Studies also reveal the interplay of more micro-macro processes and biographical aspects that may shape inequality beliefs (see Summers et al 2022). For example, using focus groups, Summers et al 2022 demonstrated that other participants' views routinely shaped their own views and participants' understandings were especially malleable around information considered unfamiliar.…”
Section: Inequality Attitudes and Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…distributional-thinking about the economy is not widely shared. Instead, as Summers et al [30] found, people tend to resort to 'heuristics' when asked to think about economic distributions, such as imagining social groups and their lifestyles. This is consistent with Savage's argument that the cultural dimensions of inequality cannot be reduced to an economic distributional grid (see e.g.…”
Section: : Building a Phenomenological Account Of Wealth: Wealth As E...mentioning
confidence: 99%